Penerapan Layanan Konseling Kelompok Teknik Realitas dalam Mengatasi Kepercayaan Diri pada Siswa SMP Negeri 29 Medan - Sari, Indah Putri; Lesmana, Gusman; Aguslina, Aguslina (LPPPI Publishing, 2025)
This classroom action research investigates the application of group counselling using Reality Therapy to address low self-confidence among ninth-grade students at SMP Negeri 29 Medan. Employing a descriptive qualitative approach through two action-reflection cycles, the intervention involved planning, implementation, observation, and reflective stages. Data were gathered via observations, checklists, field notes, and student reflections, then analysed following Miles and Huberman’s model of data reduction, data display, and conclusion drawing. Findings reveal that after the Reality Therapy sessions, at least 75% of participants demonstrated significant gains in self-confidence, active classroom participation, and perceived ability to manage academic challenges. Limitations include time constraints for deeper intervention and external factors such as family support. Overall, Reality Therapy in group counselling proved effective in enhancing students’ self-confidence and offers a replicable model for school counselling programs.